Organizational Culture in Islamic Education: An Analysis of Values, Structure, and Its Implications for Improving Educational Quality - Jaswadi Jaswadi (Journal of Education and Learning Sciences, 2026)
This study examines organizational culture in Islamic education through an integrative analysis of values, organizational structure, and their implications for improving educational quality. The study was motivated by the growing demand for Islamic educational institutions to strengthen institutional quality while maintaining Islamic values amid the challenges of globalization and digital transformation. This research employed a library research approach using an integrative literature review strategy to synthesize contemporary scientific studies related to organizational culture in Islamic education. Data sources were obtained from scholarly journals, books, and academic publications indexed in reputable databases published between 2021 and 2026. The analysis was conducted through thematic analysis and narrative synthesis to identify conceptual patterns concerning the relationship between values, organizational structures, and educational quality. The findings indicate that organizational culture in Islamic education is formed through the integration of spiritual, ethical, and social values institutionalized within organizational structures and educational practices. Islamic values such as tauhid, amanah, integrity, and ukhuwah function as normative foundations that shape collective behavior and institutional orientation. Furthermore, organizational structures based on participatory and value-oriented leadership strengthen the implementation of these values in educational management. The study also reveals that a strong organizational culture contributes significantly to improving educational quality through enhanced teacher performance, conducive learning environments, and holistic student character development. This study offers a conceptual contribution by formulating an integrative model of organizational culture in Islamic education that connects values, structure, organizational culture, and educational quality within a unified analytical framework.